Is uneven-aged silviculture best for maximizing ecosystem functioning, services, biodiversity, and resilience in Walloon forests? - Frédéric André; Arthur Guignabert; Hugues Goosse; François de Coligny; Gauthier Ligot; Benoit Courbaud; Mathieu Fortin; Mathilde Pau; Sylvain Marchi; Mathieu Jonard (Regional Environmental Change, 2026)

Modeling productivity of silver birch (Betula pendula Roth.) combining phytocentric and geocentric approaches in Northwestern Europe - Lorna Zeoli; Tom De Mil; Aurélien Forler; Mathilde Pau; Nicolas Latte; Hugues Claessens; Gauthier Ligot (Forest Ecology and Management, 2025)

Site index as a predictor of the effect of climate warming on boreal tree growth - Mathilde Pau; Sylvie Gauthier; Raphaël D. Chavardès; Martin P. Girardin; William Marchand; Yves Bergeron (Global Change Biology, 2022)
The boreal forest represents the terrestrial biome most heavily affected by climate change. However, no consensus exists regarding the impacts of these changes on the growth of tree species therein. Moreover, assessments of young tree responses in metrics transposable to forest management remain scarce. Here, we assessed the impacts of climate change on black spruce ( Picea mariana [Miller] BSP) and jack pine ( Pinus banksiana Lambert) growth, two dominant tree species in boreal forests of North America. Starting with a retrospective analysis including data from 2591 black spruces and 890 jack pines, we forecasted trends in 30‐year height growth at the transitions from closed to open boreal coniferous forests in Québec, Canada. We considered three variables: (1) height growth, rarely used, but better‐reflecting site potential than other growth proxies, (2) climate normals corresponding to the growth period of each stem, and (3) site type (as a function of texture, stoniness, and drainage), which can modify the effects of climate on tree growth. We found a positive effect of vapor pressure deficit on the growth of both species, although the effect on black spruce leveled off. For black spruce, temperatures had a positive effect on the height at 30 years, which was attenuated when and where climatic conditions became drier. Conversely, drought had a positive effect on height under cold conditions and a negative effect under warm conditions. Spruce growth was also better on mesic than on rocky and sub‐hydric sites. For portions of the study areas with projected future climate within the calibration range, median height‐change varied from 10 to 31% for black spruce and from 5 to 31% for jack pine, depending on the period and climate scenario. As projected increases are relatively small, they may not be sufficient to compensate for potential increases in future disturbances like forest fires.